Innovative Basis of Improvement of Professional Development System of Higher Education Institution Pedagogical Staff - Begimkulov, Uzokboy; Shoymardonov, Tuymurod; Adashboev, Shavkiddin; Obidov, Azamat; Eshmamatov, Ismoil (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article highlight’s innovative approaches of organizing pedagogical staff professional development in higher education system of the Republic of Uzbekistan. The essence of integrative model of distance professional development, continuous system of higher education pedagogical staff’s professional development is being described there.